Extraction and Application of Avocado (Persea americana Mill.) Seed Tannins as a Biomordant for Natural Dyeing of Timorese Handwoven Fabric - Adu, Risna Erni Yati; Djugian Gelyaman, Gebhardus; Nensiana Kono Foni, Elfrida; Theresia Djue Tea, Marselina (Al-Kimia, 2023)
Natural dyeing of Timorese handwoven fabrics results in less intense and less color fastness of products against washing. The use of metal mordant such as alum for color fixation is not sufficiently safe for the environment. In this study, the extracted tannin of avocado seeds was applied as an alternative mordant to increase the color fastness of natural handwoven fabrics. Tannin was extracted by maceration, qualitatively and quantitatively analyzed with UV-Vis, applied in different concentration for handwoven fabric dyeing and the color fastness value was determined using the Staining Scale Standard. The results revealed that avocado seeds contain tannins with a total tannin content of 22.75 mg/kg dry weight. The FTIR Spectra shows several specific functional groups of tannin such as C-O and -OH which are effective enough to bind dyes and fabric fibers. It was concluded that the higher the tannin concentration, the higher the color fastness of the handwoven fabrics.